TERAPI SIKLOFOSPAMID PADA PASIEN ANEMIA APLASTIK DI RSHAM - Julahir H Siregar (Jurnal Penelitian Kesmasy, 2018)
Aplastic anemia is a disorder of the clinical syndrome which is characterized by red blood cell deficiency, neutrophils, monocytes and platelets without any other form of marrow damage. Patients in the study included poly hematologic oncology patients and RSHAM inpatients who had been diagnosed with aplastic anemia and had 4 cycles of chemotherapy with cycloposfamide. Data was collected retrospectively, which included: personal data, how many cycles followed cycloposphamide therapy, hemoglobin, leukocytes, platelets before and after chemotherapy and how many PRCs and platelets were given. In this study involved too few patients and most patients were not tested for bone marrow examinations for evaluation. Before cycloposfamide therapy is given a cytogenetic examination is not performed. From the data above, we cannot conclude whether cycloposfamide therapy given in RSHAM gives a good response or not.